A Nanofiber Mat With Dual Bioactive Components and a Biomimetic Matrix Structure for Improving Osteogenesis Effect - Han, Yadi; Shen, Xiaofeng; Chen, Sihao; Wang, Xiuhui; Du, Juan; Zhu, Tonghe (Frontiers in Chemistry, 2021)
The challenge of effectively regenerating bone tissue through tissue engineering technology is that most tissue engineering scaffolds cannot imitate the three-dimensional structure and function of natural extracellular matrix. Herein, we have prepared the PLLA-based dual bioactive components reinforced nanofibers mat were named as PLLA/BSA/nHAp with dual bioactive components by combined homogeneous blending and electrospinning technology. The results showed that these nanofibers mats had sufficient mechanical properties and porous structure suitable for cell growth and migration. Furthermore, the results of cell experiments in vitro showed that PLLA/BSA/nHAp composite nanofibers mat could preferably stimulate the proliferation of MC3T3 cells compared with pure PLLA nanofibers mat. Based on these results, the scaffolds developed in this study are considered to have a great potential to be adhibited as bone repair materials.